Simulasi dan Analisis Unjuk Kerja Plts Atap Off-Grid Terinstal Supercapacitor - Taneza, Erlan; Nrartha, I Made Ari; Nababan, Sabar; Hasibuan, Arnawan (VOCATECH: Vocational Education and Technology Journal, 2024)
AbstractThe reliability of off-grid solar power systems (PLTS) is highly dependent on battery performance. However, the battery shows limited response in supplying the load due to unstable voltage fluctuations, which causes the battery to heat up quickly. So there is a need for additional components in the system such as supercapacitors. Supercapacitors are energy storage devices with high power and energy density, short charging duration, long service life, and low risk of heat. This research aims to determine the effect of supercapacitors on the performance of off-grid PLTS systems. The research uses data from the specifications of the off-grid rooftop PLTS system at SMKN 1 Lingsar. Temperature and irradiation data are obtained from the data logger installed in the system. The research is a simulation in Simulink MATLAB. Several supercapacitor capacities were selected to determine changes in system performance. The simulation results show that the supercapacitor capacity has a significant effect on the current and voltage in the battery. Supercapacitors show the ability to absorb and release large currents in a relatively short time, thereby speeding up the battery charging process. Supercapacitors with a capacity equivalent to battery capacity have the best contribution to system performance. Keywords:Batteries; Off-grid Rooftop PV System; Supercapacitor. AbstrakKeandalan sistem tenaga surya (PLTS) off-grid sangat bergantung pada kinerja baterai. Namun, baterai menunjukkan respons yang terbatas dalam menyuplai beban karena fluktuasi tegangan yang tidak stabil, yang menyebabkan baterai menjadi cepat panas. Sehingga perlu adanya komponen tambahan pada sistem seperti superkapasitor. Superkapasitor adalah perangkat penyimpanan energi dengan daya dan kepadatan energi tinggi, durasi pengisian daya yang singkat, masa pakai yang lama, serta risiko panas yang rendah. Penelitian ini bertujuan mengetahui pengaruh supercapasitor pada kinerja sistem PLTS off-grid. Penelitian menggunakan data dari spesifikasi sistem PLTS atap off-grid di SMKN 1 Lingsar. Data suhu dan iradiasi diperoleh dari data logger yang terpasang pada sistem. Penelitian merupakan simulasi pada Simulink MATLAB. Beberapa kapasitas supercapasitor dipilih untuk mengetahui perubahan kinerja sistem. Hasil simulasi menunjukkan bahwa kapasitas superkapasitor berpengaruh signifikan terhadap arus dan tegangan pada baterai. Superkapasitor menunjukkan kemampuan menyerap dan melepaskan arus besar dalam waktu relatif singkat sehingga mempercepat proses pengisian baterai. Superkapasitor berkapasitas setara kapasitas baterai mempunyai konstribusi terbaik pada kinerja sistem.  Kata Kunci:             Baterai, Sistem PV Atap Off-grid, Superkapasitor.